Evaluation of Superoxide Dismutase and Some Biochemical Parameters as a Vital Biomarker in Breast Cancer Patients - Abd Al-Latif, Nabaa Haider; Maher, Firas Taher; abed, Nazar A. N. (Hammurabi Journal of Medical Sciences, 2024)
Background: breast cancer is defined as the uncontrollable development of breast cells, second highest cause of cancer-related deaths in the world. Objective: estimate the activity of (SOD), levels of liver function (ALP, GOT and GPT), prolactin and the level of magnesium in the blood of women breast cancer with compared with control women. Materials and Methods: This study was conducted on 90 women (60 patients and 30 controls). Patients were referred to the Oncology Teaching Hospital/Medical City, during the period from 2023 to 2024. Results: significantly decrease (P<0.01) in the level of (SOD)the level of prolactin hormone at p-value (P<0.05) activity in BC patients comparison with healthy women, and significant elevation in the level of : (ALP) and (GPT)at (P<0.01) in BC patients comparison with control group while the levels of magnesium and(GOT) were appeared at the normal range P>0.05. Conclusion: The results showed a decrease in the level of SOD due to oxidative stress and negative changes in prolactin in breast cancer patients compared to the control group, with increased levels of GPT and ALP, which may indicate the presence of a malignant tumor. In contrast, no significant differences were observed in the levels of magnesium and GOT between patients and healthy individuals. This study is considered a vital indicator and a tool for diagnosing and detecting disease.